Implementation of the Healthy Community Movement (GERMAS) through the ownership of sanitary toilets - Yuzuar Afrizal; Muria Herlina (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2023)
Improper disposal of fecal matter in inappropriate locations can lead to environmental pollution, various diseases, and even death. This community service project focused on assisting farmer groups in Air Pesi Village, Kepahiang District, Bengkulu Province, who lacked proper sanitation facilities. Initially, the goal was to build two sanitary toilets, but this was expanded to four through cost-effective communal labor. Pre-and post-test assessments showed a substantial increase in residents' knowledge of healthy behaviors and the Healthy Living Community Movement in Indonesia known as Gerakan Masyarat Hidup Sehat (GERMAS) principles, from 32% before the intervention to 89% afterward. Additionally, the project successfully exceeded its target by constructing four sanitary toilets, which were not only used for waste disposal but also as bathing and laundry facilities. Community awareness of GERMAS principles increased by 57%. This initiative can serve as a model for local residents and inform government policies on rural sanitation. This project highlights the importance of community-driven sanitation improvements in rural areas.